QUEERING THE GENDER CODES IN TÜRKIYE: ZEKI MÜREN AS A TRANSLATIONAL PRESENCE - Marmara, Fulya; Gorguler, Zeynep Suter (UNIV FEDERAL PARAIBA, 2025)
This article examines the performative reconfiguration of binary gender codes through the artistic persona of Zeki M & uuml;ren, framed within the context of cultural translation. Zeki M & uuml;ren (1931-1996), a renowned Turkish singer, composer, and cultural icon, was celebrated for his androgynous image, distinctive voice, and transformative contributions to both Turkish classical and contemporary music. His self-presentation and performances are seen as acts that challenged traditional portrayals of masculinity and femininity, disrupting dominant gender norms in T & uuml;rkiye since the 1950s. Drawing on Sarah Maitland's theory of cultural translation and Judith Butler's concept of gender performativity, the study adopts a multimodal thematic approach to analyze M & uuml;ren's fluid identity and aesthetic expression. Special attention is given to his linguistic and lyrical choices, use of pseudonyms, performative gestures, and especially the stage costumes he either designed or meticulously curated. These elements are explored as acts of cultural translation that negotiate between traditional gender codes and emergent queer possibilities, with the costumes functioning as visual texts that enrich the analysis of gender through their symbolic and theatrical dimensions. Ultimately, the article argues that M & uuml;ren subverted heteronormative structures and expanded the imaginative space for queer identity within T & uuml;rkiye's socio-cultural landscape, a context marked by both deeply conservative gender norms and a distinctive receptivity to his singular public persona.
Keywords: Queer translation; Binary gender codes; Performativity; Cultural translation; Zeki M & uuml; ren; Women's Studies